Machineology as a conceptual basis for the formation of a mining engineering scientific platform - Glushchenko, V V (IOP conference series. Earth and environmental science, 2019)
The subject of research is mining machineology as a methodological basis of a scientific platform in mining engineering. The object of research is a scientific platform in mining engineering. The purpose of the work is to increase the efficiency of mining engineering methods. As a result of the study, the importance of mechanical engineering for the formation of a scientific platform in mining mechanical engineering is revealed. The obtained results contribute to increasing the effectiveness of scientific and innovative activities. The result of an innovative project in mining engineering was achieved, taking into account the increased efficiency of using the results of scientific research.